Stress distribution and resistance of lap splices under fatigue loading. (15th November 2018) - Zanuy, Carlos; Díaz, Iván M.
Highlights: The bond stress distribution is non-uniform along the embedded length of lap splices. Fatigue strength from S-N models and uniform stress assumption is not accurate. A redistribution of stresses develops with load cycles until final fatigue failure. Abstract: Straight lap splices are employed in reinforced concrete to transfer loads from one steel reinforcing bar to another by bond between the embedding concrete and the two bars along a lapped length. In the last years, some concerns have arisen on the possibility of fatigue of bond-related structural problems, in part due to the very few models available to evaluate the bond fatigue strength. Regarding design standards, some codes for off-shore structures have addressed such a specific topic, by means of a simple S-N formulation. Besides that, recent experimental research has shown that fatigue failures of lap splices can occur because of the poor confinement conditions which result in a small static bond strength leading to high relative stress levels sensitive to fatigue. In the present paper, a mechanical model is proposed to understand the fatigue behaviour of lap splices. The model solves the lap splice problem by taking into account the particular equilibrium, compatibility, constitutive and boundary equations, which produce a different solution than other bond-related problems (anchorages, tension stiffening) in terms of stress distribution along the lapped length. For the local bond-slip behaviour, a cycle-dependent formulation is used for the increase of slip with load cycles and the fatigue failure criterion. The model is able to reproduce the real bond stress distribution, which is nonuniform along the lapped length, and the process of redistribution that takes place with load cycles. It is shown that the redistribution process is responsible for higher fatigue strength than that calculated under the assumption of uniform stress distribution.